2012
DOI: 10.1111/j.1600-0501.2012.02523.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of plaque accumulation and soft‐tissue blood flow with the use of full‐arch implant‐supported fixed prostheses with mucosal surfaces of different materials: a randomized clinical study

Abstract: In terms of oral hygiene and mucosal inflammation, titanium was superior to reinforced composite resin in implant-supported fixed prostheses for edentulous subjects, and the short-term use of acrylic resin was superior to the use of reinforced composite resin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 38 publications
2
24
0
Order By: Relevance
“…Although, the search strategy was broadened possible eligible publications (Larsson & Vult von Steyern 2010;Larsson & Vult Von Steyern 2013)which the authors were aware ofwere missed. While scrutinizing these two papers, the authors realized that the search terms that have been applied were Jemt et al (1999) Sample size per study arm Balshi et al (2012) Study design Becker et al (2000) No characteristics on restorations Borges et al (2012) No characteristics on restorations Ericsson et al (2000) No characteristics on restorations Di Giacomo et al (2012) Sample size/study design € Ortorp & Jemt (2000) Interim results of included study Ercoli et al (2012) Study design/sample size € Ortorp & Jemt (2002) Interim results of included study Furze et al (2012) Sample size Henriksson & Jemt (2003) Sample size per study arm Giordano et al (2012) Sample size Romeo et al (2003) Study design/no CAD/CAM prostheses Meloni et al (2012) Quality of reporting Engquist et al (2004) Follow-up, study design Tahmaseb et al (2012) No characteristics on restorations/follow-up € Ortorp & Jemt (2004) Interim results of included study Biscaro et al (2013) Sample size van Steenberghe et al (2005) Study design/no CAD/CAM restorations Lin et al (2013) No characteristics on restorations Gallucci et al (2007) Sample size/study design Cordaro et al (2013) No characteristics on restorations Malo et al (2007) Study design/sample size Kanao et al (2013) No characteristics on restorations/sample size Sanna et al (2007) No characteristics on prostheses Katsoulis et al (2013) No response/quality of reporting Vafiadis (2007) Case report/study design (2010) Sample size/study design Alfadda (2014) In vitro design…”
Section: Discussionmentioning
confidence: 99%
“…Although, the search strategy was broadened possible eligible publications (Larsson & Vult von Steyern 2010;Larsson & Vult Von Steyern 2013)which the authors were aware ofwere missed. While scrutinizing these two papers, the authors realized that the search terms that have been applied were Jemt et al (1999) Sample size per study arm Balshi et al (2012) Study design Becker et al (2000) No characteristics on restorations Borges et al (2012) No characteristics on restorations Ericsson et al (2000) No characteristics on restorations Di Giacomo et al (2012) Sample size/study design € Ortorp & Jemt (2000) Interim results of included study Ercoli et al (2012) Study design/sample size € Ortorp & Jemt (2002) Interim results of included study Furze et al (2012) Sample size Henriksson & Jemt (2003) Sample size per study arm Giordano et al (2012) Sample size Romeo et al (2003) Study design/no CAD/CAM prostheses Meloni et al (2012) Quality of reporting Engquist et al (2004) Follow-up, study design Tahmaseb et al (2012) No characteristics on restorations/follow-up € Ortorp & Jemt (2004) Interim results of included study Biscaro et al (2013) Sample size van Steenberghe et al (2005) Study design/no CAD/CAM restorations Lin et al (2013) No characteristics on restorations Gallucci et al (2007) Sample size/study design Cordaro et al (2013) No characteristics on restorations Malo et al (2007) Study design/sample size Kanao et al (2013) No characteristics on restorations/sample size Sanna et al (2007) No characteristics on prostheses Katsoulis et al (2013) No response/quality of reporting Vafiadis (2007) Case report/study design (2010) Sample size/study design Alfadda (2014) In vitro design…”
Section: Discussionmentioning
confidence: 99%
“…However, the reaction of soft peri-implant tissues to composite is a major concern. A randomized clinical trial showed that composite resin surfaces harbored a marked plaque accumulation, which produced mucosal inflammation in many cases, in comparison with titanium (Kanao et al 2013). Therefore, the use of resin composite abutments remains limited.…”
mentioning
confidence: 99%
“…The laser speckle contrast imager (LSCI) is a more recent advancement in microvascular imaging, which proved to be useful in measuring the microcirculation of the human gingiva with high spatial and temporal resolution simultaneously . Taking the opportunity provided by the high spatial resolution, a new method was designed to study the remote effects of various drugs when applied to a small restricted area on the human gingiva.…”
Section: Introductionmentioning
confidence: 99%
“…The laser speckle contrast imager (LSCI) is a more recent advancement in microvascular imaging, which proved to be useful in measuring the microcirculation of the human gingiva with high spatial and temporal resolution simultaneously. [33][34][35] Taking the opportunity provided by the high spatial resolution, a new method was designed to study the remote effects of various drugs when applied to a small restricted area on the human gingiva. Our aim was to use this method to investigate the remote effect of local vasodilation evoked by the topical application of NO donor to ascertain the presence of spreading vasodilation in the human gingiva.…”
Section: Introductionmentioning
confidence: 99%